2013
DOI: 10.1128/jvi.00012-13
|View full text |Cite
|
Sign up to set email alerts
|

Griffithsin Protects Mice from Genital Herpes by Preventing Cell-to-Cell Spread

Abstract: e Griffithsin, which binds N-linked glycans on gp120 to prevent HIV entry, has the most potent HIV-1 inhibitory activity described for any antiviral lectin and is being developed for topical preexposure prophylaxis. The current studies were designed to further assess its potential by exploring its activity against herpes simplex virus 2 (HSV-2), a cofactor for HIV acquisition, in vitro and in a murine model. Safety was evaluated by examining its impact on epithelial barrier integrity in polarized cultures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
153
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(158 citation statements)
references
References 54 publications
4
153
0
1
Order By: Relevance
“…The increased susceptibility was associated with modest increases in inflammatory mediators in the genital tract and disruption of the epithelial barrier. In contrast, 1% TFV gel, 0.5% PRO 2000, and 0.1% griffithsin gel did not increase the risk of HSV infection in this model (15,17,19). These findings suggest that this relatively inexpensive small-animal model may provide a biomarker of microbicide safety.…”
mentioning
confidence: 67%
“…The increased susceptibility was associated with modest increases in inflammatory mediators in the genital tract and disruption of the epithelial barrier. In contrast, 1% TFV gel, 0.5% PRO 2000, and 0.1% griffithsin gel did not increase the risk of HSV infection in this model (15,17,19). These findings suggest that this relatively inexpensive small-animal model may provide a biomarker of microbicide safety.…”
mentioning
confidence: 67%
“…We observed that all EFs were nontoxic to cells in all three vaginal cell lines, with the cells showing greater than 93% viability after treatment, indicating their potential for future translation in vivo. We expected favorable cytotoxicity results, as a feature of this platform is that an FDA-approved polymer is used with the promising biologic GRFT, which has demonstrated outstanding safety profiles both in vitro and in vivo (46,56). These results are particularly important for translation in vivo, as cytotoxicity and inflammation have been shown to increase the propensity for infection in clinical trials (2)(3)(4)(5)7).…”
Section: Discussionmentioning
confidence: 99%
“…For the adhesive surface moiety, the biological antiviral lectin GRFT was selected, as it has been demonstrated to bind to and to have antiviral efficacy against a variety of viruses, including HIV-1 and HSV-2 (44)(45)(46)(47)(48)(49)(50)(51). Previous work by our groups has demonstrated that GRFT has an exceptionally potent HIV-1-inhibitory capability as a multivalent front-line HIV entry inhibitor (49)(50)(51)(52)(53)(54), and of the biologically based inhibitors, GRFT has exceptionally potent anti-HIV activity, inactivating HIV-1 immediately upon contact (51,52).…”
mentioning
confidence: 99%
See 2 more Smart Citations